Art appreciation - Solmerano, Ernesto Thaddeus M. (Mandaluyong City : Books Atbp. Publishing Corp., 2019)
This book aims to develop in students the ability to appreciate, analyze, and critique works of art. Through interdisciplinary, multimodal and outcome-based education approaches, the book intends to enhance students' understanding and appreciation of the arts by providing them with opportunities to explore and experience the diversity and richness of the arts. This book intend to reaffirm the value of the arts as we embark on a journey into the millenium. It is intended to convey the fervent hope that, as we glory in the new technological wonders, we will not forget that being human - in the total sense - involves the balancing of the need of out physical beings and the strengthening of our human spirits and the making of our souls.
Unit 1 The nature of art -- Unit 1 Learning competencies -- Unit 1 Research starter -- Lesson 1: What is Art? -- Lesson 2: Some basic assumptions about art -- Lesson 3: Basic art criticism -- Lesson 4: The artist and the artisan -- Unit 2 Describing the world of art -- Unit 2 learning competencies -- Unit 2 Research starter -- Lesson 5: Subject and content in art -- Lesson 6: Function in the arts -- Unit 3 Learning how art is made -- Unit 3 Learning competencies -- Unit 3 Research starters -- Lesson 7: Medium and technique in the arts -- Lesson 8: Organization in the arts -- Unit 4 Art through the ages -- Unit 4 Learning competencies -- Unit 4 Research starters -- Lesson 9: The History of art -- Unit 5 Living with art -- Unit 5 Learning competencies -- Unit 5 Research starters -- Lesson 10: Soul-making -- Lesson 11: Appropriation in art -- Lesson 12: Installation art -- Lesson 13: Philippine traditional motifs and crafts -- Lesson 14: All about Okir -- Lesson 15: Fusion in the arts : classical music and film -- Lesson 16: From art to art -- Unit 6 Experiencing art -- Unit 6 Learning competencies -- Unit 6 Research starters -- Lesson 17: Art museum and art gallery
Inlcudes bibliographical references.
Keywords: ART APPRECIATION